Dampak Pandemi Covid-19 Terhadap Dunia Pendidikan - Siahaan, Matdio (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2020)
Indonesia is one of the countries infected with the Covid-19 pandemic. Corona virus 2019 (COVID-19) is an infectious disease caused by acute corona virus 2 respiratory syndrome (SARS-CoV-2). So that the impact on the community and students can not meet directly on campus or in public places. Based on Nielsen's research entitled